Preliminary study on the role of serum PECAM-1 in metastatic breast cancer - Zheng, Lin-Feng; Chen, Pei; Wang, Zeng; Wang, Xiao-Jia; Lei, Lei (Translational Cancer Research; Vol 6, No 6 (December 28, 2017): Translational Cancer Research, 2017)
Background: The metastatic breast cancer (MBC) is yet incurable with high mortality, thereby requiring improved biomarkers for predicting the outcome of palliative therapy in patients. The present study evaluated the correlation of serum platelet and endothelial cell adhesion molecule-1 (PECAM-1) with the prognosis of MBC patients. Methods: Thirty women initially diagnosed as MBC before any palliative treatment, were divided according to the median value of serum PECAM-1 level, Group A (4,058.89 pg/mL). After median 78 months follow-up from the preliminary surgery, 15 patients died of breast cancer. The Kaplan-Meier method and Cox regression analysis were used to determine progressionfree survival (PFS) and overall survival (OS) rates. Other data were analyzed by the chi-square test and t-test. Results: The 3-year survival of MBC patients in Group A was higher than Group B. More patients in Group B accepted the adjuvant endocrine therapy than Group A. The serum CA125 level was higher in Group A than Group B. The serum total cholesterol (TC), low-density lipoprotein (LDL), and fasting glucose were significantly higher in Group A than Group B patients (P=0.02, P